2001
DOI: 10.1364/josaa.18.002607
|View full text |Cite
|
Sign up to set email alerts
|

Role of light intensification by cracks in optical breakdown on surfaces

Abstract: The intensity distribution of an initially plane light wave incident on planar and conical surface cracks is calculated numerically by using a wave propagation computer code. The results show that light intensity enhancements caused by interference of internal reflections at the crack and the surface are very sensitive to the light polarization, the beam angle of incidence, and the crack geometry (e.g., crack width and orientation with the surface). The light intensity enhancement factor (LIEF) can locally rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(99 citation statements)
references
References 16 publications
2
97
0
Order By: Relevance
“…Earlier studies have shown that electrical field intensification within multilayer layer high reflector interference coatings can occur due to embedded nodular defects or defective pits [12,15]. Electric field intensification within fused silica cracks has also been attributed to reduced laser damage resistance [16]. To elucidate if the coating distorted by substrate scratches can lead to electrical field intensification within the dielectric multilayer, we first collect the crosssectional image of the hafnia-silica multilayer coating on top of a substrate etched sleek ( Figure 5 (a), and then estimate the electrical-field distribution of the coating using the aforementioned simulation code.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that electrical field intensification within multilayer layer high reflector interference coatings can occur due to embedded nodular defects or defective pits [12,15]. Electric field intensification within fused silica cracks has also been attributed to reduced laser damage resistance [16]. To elucidate if the coating distorted by substrate scratches can lead to electrical field intensification within the dielectric multilayer, we first collect the crosssectional image of the hafnia-silica multilayer coating on top of a substrate etched sleek ( Figure 5 (a), and then estimate the electrical-field distribution of the coating using the aforementioned simulation code.…”
Section: Resultsmentioning
confidence: 99%
“…A number of mechanisms have been proposed for damage site growth which may explain this discrepancy: namely residual stress which drives crack propagation, the sub-bandgap absorption of the incident pulse energy by electronic defects [ (Skuja 1998)], field intensification brought about by surface roughness [ (Genin, Salleo et al 2001)], and reduced mechanical strength due to the presence of cracks [ (Dahmani, Lambropoulos et al 1999)]. Next, we investigate the differences in how these phenomena present themselves in as-initiated sites versus sites with a number of laser exposures in order to try to explain the difference in growth rate following anneal.…”
Section: Discussionmentioning
confidence: 99%
“…7,[16][17][18] Surface morphology with these isolated flaws, even not so large in number, would greatly modulate the incident laser and correspondingly produce light intensification up to hundreds of times. 18,19 It is well known that the electronic ionization rates, which determine the intrinsic laser damage mechanisms, are highly intensity-dependent.…”
Section: -3mentioning
confidence: 99%